Relationship between bladder cancer and polymorphisms of OX40 (rs17568) and OX40L (rs1234313) genes in a Turkish population - Osman Bilen; Levent Verim; Cagatay Tosun; Omer Yuksel; Ulgen Sever; Dilara Sonmez; Mehmet Tolgahan Hakan; Ilhan Yaylim (Biotechnology & Biotechnological Equipment)
The aim of this study was to investigate a possible association between the variations and effects of gene changes in the OX40/OX40L pathway and the risk of developing bladder cancer in a Turkish population. The study included 104 patients with bladder cancer and 97 healthy individuals. The distribution of OX40 (rs17568) and OX40L (rs1234313) polymorphisms was evaluated by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). The genotype distributions of OX40 rs17568 regions showed non-significant differences between the patient and control groups (p = 0.256). No difference was also found in T2 invasive tumours, high, and low-grade tumours. The genotype distributions of the OX40L rs1234313 region were significantly different between the patient and control groups (p = 0.023). The frequency of the GG genotype and homozygous GG/AA genotypes was higher among the patients than in the control group, and the difference was significant (for GG genotype: OR 0.462; 95% CI 0.255–0.835; p = 0.010; for GG/AA genotype: OR 0.456 (0.257–0.808; p: 0.007). The OX40L A allele (AA/AG) had higher frequency in T2 invasive bladder cancer patients than in those with T1 and Ta (p = 0.028). There was no statistically significant difference in the OX40L genotype distributions among the graded tumour groups (p = 0.689). The results indicate that the rs1234313 A/G gene polymorphism may contribute to the development of bladder cancer in this Turkish population. Further observations in a larger cohort need to confirm this suggestion.